Daytime napping, comorbidity profiles, and the risk of sarcopenia in older individuals - Hu, Zhigang; Yang, Ailan; Tian, Yufeng; Song, Xinyu (Frontiers in Physiology, 2022)
Appropriate daytime napping is associated with the decreased risk of cerebro-cardiovascular diseases, but whether daytime napping affects sarcopenia remains to explore. Our study plains to examine the associations between sarcopenia with daytime napping and comorbidity. Study population came from the China Health and Retirement Longitudinal Study 2011 to 2015. Latent class analysis (LCA) was used to identify comorbidity profiles based on fourteen doctor-diagnosed chronic diseases. Subsequently, smooth function and restricted cubic spline with three binomial regression models determined the associations between sarcopenia with daytime napping and comorbidity profiles. About 18.7% (2894) and 5.4% (832) of 15404 individuals were diagnosed with sarcopenia and severe sarcopenia. LCA delineated four classes as the best fit as follows: dominant heart diseases or risks (class 1, N=2203), dominant chronic lung diseases (class 2, N=740), minimal or least diseases(class 3, N=10612, reference), and dominant digestive diseases and rheumatism (class 4, N=1849). Compared with reference group (class 3), the multivariate-adjusted ORs (95%CIs) of sarcopenia in model 3 were 0.72(0.60-0.88) for class 1, 1.17 (0.92-1.51) for class 2, and 0.92 (0.77-1.09) for class 4. Smooth function and restricted cubic spline suggested that individuals who napped about 60 minutes seemingly had the lowest risk of sarcopenia. Individuals who napped for 1 to 59 minutes (adjusted OR=0.80, 95%CI:0.68-0.94) and 60 to 119 minutes (adjusted OR=0.83, 95%CI: 0.72-0.95) had the significantly lower risk of sarcopenia but not severe sarcopenia than those with no napping. Insufficient and excessive daytime napping might be associated with the increased risk of sarcopenia, especially in individuals with dominant chronic lung diseases profile.